TRENDS IN CONTEMPORARY PAINTINGS - Nimbolkar, Vivek; Khade, Alka (International Journal of Research -GRANTHAALAYAH, 2019)
Before there was an art of abstract painting, it was already widely believed that the value of a picture was a matter of colors and shapes alone. Music and architecture were constantly held up to painters as examples of a pure art which did not have to imitate objects but derived its effects from elements peculiar to itself. But such ideas could not be readily accepted, since no one had yet seen a painting made up of colors and shapes, representing nothing. If pictures of the objects around us were often judged according to qualities of form alone, it was obvious that in doing so one was distorting or reducing the pictures; you could not arrive at these paintings simply by manipulating forms. And in so far as the objects to which these forms belonged were often particular individuals and places, real or mythical figures, bearing the evident marks of a time, the pretension that art was above history through the creative energy or personality of the artist was not entirely clear. In abstract art, however, the pretended autonomy and absoluteness of the aesthetic emerged in a concrete form. Here, finally, was an art of painting in which only aesthetic elements seem to be present.